LDL receptor-peptide conjugate as in vivo tool for specific targeting of pancreatic ductal adenocarcinoma - Angélina Acier (Nature Portfolio, 2021)
Acier et al. investigated a peptide cargo system, the Fc(A680)-VH4127, that targets PDAC through the LDLR cell-surface receptor. The Fc(A680)-VH4127 was found to specifically target spontaneous pancreatic tumors in KICmice, as well as metastatic pancreatic tumors in liver.